Щодо визначення критичної довжини кабельної лінії електропередавання. Коментарі та зауваження до глави 2.3 ПУЕ - Буйний, Роман Олександрович; Зорін, Владлен Володимирович; Квицинський, Анатолій Олександрович (НТУ "ХПІ", 2010)
Проаналізовано вплив ємності високовольтних ЛЕП на режим напруги. Отримано аналітичну залежність, що дозволяє розраховувати критичну довжину КЛ, за якої, при відключенні навантаження, напруга в кінці лінії не буде перевищувати допустиму напругу для ізоляції кабелю. Це дозволило обґрунтувати доцільність зміни у розділі 2.3 ПУЕ формули для визначення критичної довжини КЛ.

The analysis of influence of capacity of high-voltage electric lines on a mode of their work is carried out. Analytical expression which allows to count critical length of the cable line at which their end voltage not exceed admissible value for cable isolation in no load operation is received. The expediency of replacement of a ratio defining critical length of the cable line in chapter 2.3 of "Rules of electro installations carry out" is proved
About definition of critical length of a cable electric line. comments and remarks to chapter 2.3 of "rules of electric installations carry out
Keywords: високовольтні ЛЕП; режим напруги; ємність фаз; активний опір; індуктивність проводів; electric installations; cable electric line; critical length; definition